Proceedings of the 18th International Symposium on Advancement of Construction Management and Real Estate - Yang, Donglang; Qian, Yanjun; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The Chinese Research Institute of Construction Management (CRIOCM) in collaboration with Xi'an Jiaotong University proudly invites all academics, researchers and professionals to participate in the CRIOCM 2013, the 18th International Symposium on "Advancement of Construction Management and Real Estate". We will uphold and preserve the idea and tradition of pragmatism and innovation, to offer an excellent academic and communication platform for academics and professionals to exchange information on the latest developments in real estate and construction management.
Sustainable Construction -- Urban Construction and Land Use -- Housing Policy and Real Estate Market Development -- Project Management and Facility Management -- Safety, Risk and Value Management in Construction -- Construction Innovation and Knowledge Management -- Traffic Planning, Logistics and Supply Chain Management -- Informatization and Information Technology in Construction -- Professional Education for Real Estate and Construction Management -- Green Construction Materials and Construction Waste Recycling -- Other themes.
Keywords: Economics; Economics/Management Science; Production/Logistics/Supply Chain Management